PENGEMBANGAN EKOSISTEM HALAL MELALUI PENGUATAN LITERASI KEUANGAN SYARIAH DAN DIGITALISASI UMKM DI DESA GUNUNG SARI - Lale Ajeng Khalifatun Wardani; Muhammad Habibullah Aminy (Nusantara Hasana Journal, 2023)
Developing a halal ecosystem is a crucial strategy for strengthening the competitiveness of MSMEs at the local level. This study aims to analyze how enhancing Sharia financial literacy and MSME digitalization supports the establishment of a halal ecosystem in Gunung Sari Village, Gunungsari District, West Lombok Regency. The study employs a qualitative descriptive approach, with data collected through observation, in-depth interviews with MSME owners, village officials, and MSME facilitators, as well as document analysis. The findings indicate that while the majority of MSME owners understand the basic concepts of halal products, their Sharia financial literacy remains limited to basic aspects such as savings and simple financing. Digital technology adoption is also suboptimal, as some business owners still rely on conventional marketing methods. Efforts to strengthen the halal ecosystem include training on Sharia financial literacy, guidance on financial record-keeping, the adoption of digital payments, social media-based marketing, and assistance with halal certification. Synergy among the village government, Sharia financial institutions, academics, and business owners has proven to be a vital factor in accelerating the transformation of MSMEs toward a sustainable halal ecosystem.